Evaluation of static load test on instrumented bored pile - Quah, Wee Keong. (2010)
The recorded load, settlement and time data provides information on the possible problems or unexpected occurrences during interpretation of the test results. Careful scrutinizing of instrumentations’ recorded data helps to validate the assumed design parameters used. Continuation of the load test until ultimate resistance is reached and combining the test result with basic soil mechanics principles will also help to optimize information about the test pile. From the analysis of the case studies, one can observe computed loads from the load distributions are not linearly proportional to the measured strains and thus will vary with depth. Secant modulus of a concrete can vary within a wide range and is a function of imposed load. Over large stress range imposed during the test, differences between the initial and final tangent modulus for the pile material can be substantial. The load distribution curves also allow one to obtain the mobilized resistances of the pile which can be further validated through comparison with SPT-N values from the borehole logs. Axial deformation of the pile also can be measured through use of tell-tale rod extensometers as they are able to provide a crude approximation of the pile’s shaft adhesion and base resistance and such estimation should not be used in the analysis due to their high unreliability.